Perometry limb volume measurement: protocol development and reliability. (December 2013) - Bulley, Catherine; Coutts, Fiona; Tan, Chee Wee
Abstract Aims: Perometry measurement of limb volume involves non-invasive optoelectronic scanning and is increasingly used due to its practicality and increasing evidence for its validity. This study aimed to develop a standardized protocol for the measurement of upper and lower limb volume using a vertical perometer (400T) and test its reliability. Methodology: Multiple pilot studies were conducted in a laboratory-based setting to investigate specific procedural questions and develop the final standardized protocol. This included elements such as standardization of the proportion of limb being measured, and of limb positioning within the perometer frame. The standardized protocol was tested for inter- and intra-rater reliability in two raters, on two separate test occasions, 24–48 h apart. The study included 30 volunteers with no known clinical conditions (n = 23 women, seven men; mean age 23). Major findings: High intra-class correlation coefficient (ICC) values resulted for intra-rater and inter-rater reliability in the upper and lower limbs (0.953–0.989). Limits of agreement analysis demonstrated less positive results, however. Principal conclusion: The results provide support for the use of this protocol to increase standardization and comparability of measurement in clinical and research contexts. Further investigation in different clinical populations is required.